This preview shows page 1. Sign up to view the full content.
Unformatted text preview: its behavior for increasing t . y + 4 y + 4 y = 0 , y (-1) = 2 , y (-1) = 1 . 4.2.14 Find the general solution of the given dierential equation. y -4 + 4 y = 0 . 4.2.22 Find the general solution of the given dierential equation. y + 2 y + y = 0 ....
View Full Document
This note was uploaded on 10/08/2010 for the course M 427K taught by Professor Fonken during the Fall '08 term at University of Texas at Austin.
- Fall '08